2020
DOI: 10.1111/ceo.13711
|View full text |Cite
|
Sign up to set email alerts
|

Low retinal toxicity of intravitreal carboplatin associated with good retinal tumour control in transgenic murine retinoblastoma

Abstract: Background: Retinoblastoma is a rare intraocular malignancy in children. Current treatments have many adverse effects. New therapeutic approaches like intravitreal injections of chemotherapies are currently being developed but their toxicities need to be evaluated on animal models. This study compares the efficacy and toxicity of intravitreal melphalan, topotecan and carboplatin, alone or in combination (sequential administration), in the LHBetaTag retinoblastoma mice. Methods: Mice were divided into nine grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Recently Lemaître et al 28 evaluated the effectiveness and safety of intravitreal injection of Melphalan, Topotecan, and Carboplatin, alone or in combination in the animal model of LHBetaTag retinoblastoma mice. They found that weekly intravitreal Carboplatin, either 1.5 or 4 μg could reduce tumor burden significantly (80%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently Lemaître et al 28 evaluated the effectiveness and safety of intravitreal injection of Melphalan, Topotecan, and Carboplatin, alone or in combination in the animal model of LHBetaTag retinoblastoma mice. They found that weekly intravitreal Carboplatin, either 1.5 or 4 μg could reduce tumor burden significantly (80%).…”
Section: Discussionmentioning
confidence: 99%
“…For the Carboplatin group, the dose chosen dose was close to the maximum tolerated dose to achieve the most effective concentration (1 µg), based on previous investigations. 28 , 30 , 31 , 32 For the Digoxin group, the dosage was chosen based on the amount of Digoxin that could result in pharmacologically active amounts in the vitreous of a rabbit (1.5 ml) for at least 4 h after injection, as well as a low systemic exposure as a proxy of cardiac toxicity for its direct impact in the translation to clinics, which was the end goal of these studies. 40 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations